Penerapan Manajemen Risiko Berbasis ISO 31000 pada Industri Fashion Kreatif: Studi Kasus Brand Uniquelymozdaily - Dea Wisnu Ramdani; Ari Assrishan Sos Mantoro; Zaid Abdul Hamid; Fajar; Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze the implementation of ISO 31000:2018-based risk management in the creative fashion industry, using a case study of Uniquelymozdaily. The implementation of risk management is crucial in dealing with market uncertainty, rapidly changing trends, and operational and reputational risks. This study used a qualitative descriptive method with a case study approach through the stages of risk identification, analysis, evaluation, and mitigation in accordance with ISO 31000 principles. The results indicate that Uniquelymozdaily faces six main risks: raw material delays, supply disruptions from suppliers, dependence on a single e-commerce platform, uncompetitive pricing strategies, ineffective marketing collaboration, and burnout due to high workload. Through the implementation of ISO 31000, the company was able to implement mitigation strategies such as supplier diversification, regular trend monitoring, and strengthening digital communication and security systems. The implementation of risk management has been proven not only to impact risk control but also to strengthen governance, increase consumer trust, and support Uniquelymozdaily's business sustainability amidst the competitive creative fashion industry.